PENGARUH KOMBINASI PENYUNTIKAN OVAPRIM DAN PGF2 α TERHADAP VOLUME SEMEN DAN KUALITAS SPERMA IKAN SELAIS (Ompok hypophthalmus) - Ridwan Manda Putra; Sukendi Sukendi; Yurisman Yurisman (Berkala Perikanan Terubuk, 2011)
This research aims to understand the effect of dosages combination ofmixed ovaprim and PGF2 α injection toward volume and quality of semen ofOmpok hypophthalmus. There were 5 treatments applied, namely A1 = 50 %ovaprim + 50 % PGF2 α/kg body weight (BW), A2 = 75 % ovaprim + 25 % PGF2α/kg BW, A3 = 25 % ovaprim + 75 % PGF2 α/kg BW, A4 = 100 % ovaprim /kgBW and A5 = 100 % PGF2 α / BW. The best combination of ovaprim and PGF2α for male fish was the A4= 100 % ovaprim (0,9 ml ovaprim/kg BW). Theaverage of semen volume produced was 0,87 ml, sperm concentration was 18,43x 10 9/ml, sperm viability was 88,67 % and sperm motility was 86,0 %.